2008
DOI: 10.3800/pbr.3.114
|View full text |Cite
|
Sign up to set email alerts
|

Non-size-selective predation on fish larvae by moon jellyfish Aurelia aurita under low oxygen concentrations

Abstract: Abstract:The moon jellyfish Aurelia aurita has increased in abundance in coastal waters around Japan during recent decades. Since the moon jellyfish is highly tolerant of low dissolved oxygen concentrations, predation impacts by moon jellyfish on zooplankton can increase during summer hypoxia in coastal waters, which is often caused by anthropogenic effects such as an increase in nutritional loading from the land. Laboratory experiments were conducted in order to test the hypothesis that summer hypoxia leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Recent laboratory experiments reported that bell contraction rate and predation rate on fish larvae by moon jellyfish under oxygen concentrations of <2 mg l -1 were similar to those under higher oxygen concentrations (4-6 mg l -1 : Shoji et al, 2005). These observations show that moon jellyfish are highly tolerant to low oxygen concentrations, as are several other jellyfish species (Breitburg et al, 1994;Keister et al, 2000;Thuesen et al, 2005), and indicate that the relative importance of trophic flow from fish larvae to moon jellyfish may increase due to changes in predator-prey interactions during summer hypoxia in coastal waters (Shoji, 2008). Understanding the distribution of the jellyfish relative to environmental conditions is therefore important in examining the potential for compensation and predation between jellyfish and fish larvae.…”
Section: Introductionsupporting
confidence: 51%
“…Recent laboratory experiments reported that bell contraction rate and predation rate on fish larvae by moon jellyfish under oxygen concentrations of <2 mg l -1 were similar to those under higher oxygen concentrations (4-6 mg l -1 : Shoji et al, 2005). These observations show that moon jellyfish are highly tolerant to low oxygen concentrations, as are several other jellyfish species (Breitburg et al, 1994;Keister et al, 2000;Thuesen et al, 2005), and indicate that the relative importance of trophic flow from fish larvae to moon jellyfish may increase due to changes in predator-prey interactions during summer hypoxia in coastal waters (Shoji, 2008). Understanding the distribution of the jellyfish relative to environmental conditions is therefore important in examining the potential for compensation and predation between jellyfish and fish larvae.…”
Section: Introductionsupporting
confidence: 51%
“…However, this factor plays a notable role only in marine areas exposed to significant desalination [39]. Also the dependence of the abundance of polyps and medusae produced by them on the level of dissolved oxygen was noted [28,29,46]. In the recent decades, the role of anthropogenic impact, including eutrophication [18,43,48], introduction of new species [27,34,45,49], and fishery [31,38], has grown considerably.…”
Section: Factors That Determine Jellyfish Biomassmentioning
confidence: 98%
“…The causes of these variations remain unclear in most cases and can be linked to climatic conditions [19,20,23,24,32,33,39], eutrophication [18,42,43,48], introduction of new species [27,34,45,49], alter ations of ecosystems related to fishery [31,38], forage resources, and other factors [28,29,46].…”
Section: Introductionmentioning
confidence: 99%
“…This in turn gives rise to a generally negative relationship between metagenic jellyfish individual size and abundance (Schneider and Behrends, 1998;Lucas, 2001), at least for Aurelia sp. Reduced competition with fish due to increased turbidity and oxygen depletion have also been proposed as mechanisms behind the prevalence of jellyfish blooms in enclosed areas, where turbidity and oxygen consumption are typically high due to increased production and surface runoff (Aksnes et al, 2004;Decker et al, 2004;Shoji, 2008;Haraldsson et al, 2012;Schnedler-Meyer et al, 2016), however we propose that retention may be an alternative or additional mechanism behind the pattern, one that indeed may work either contrary to or in concert with other mechanisms (see Sørnes et al, 2007 for an interesting example).…”
Section: Discussionmentioning
confidence: 79%